Interferensi Bahasa Indonesia dalam Pembelajaran Bahasa Arab di Pondok Pesantren Fathul Hidayah Pangean Lamongan - Mohammad Makinuddin (Jurnal Pendidikan Indonesia, 2025)
This research aims to examine the forms of Indonesian language interference in Arabic language learning at Pondok Pesantren Fathul Hidayah Pangean Lamongan, the contributing factors, and to formulate effective learning solutions to address such interference. The method used is qualitative with a case study approach through observation, interviews, and documentation over six months. The results indicate that interference occurs in phonological, morphological, syntactic, and lexical aspects, affecting students' Arabic language proficiency. The factors causing interference include the habitual use of Indonesian in daily life, limited Arabic vocabulary, differences in Indonesian dialects among students, and a learning environment that does not sufficiently support intensive Arabic usage. The proposed solutions involve implementing communicative and contextual learning methods with active Arabic speaking and writing exercises, corrective strategies, and the use of interactive learning media and language technology. The implication of this research is the importance of developing Arabic language learning methods that can reduce interference to effectively and sustainably enhance Arabic language competence in pesantren.